2014
DOI: 10.1136/heartjnl-2013-305124
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hyperaemic microvascular resistance on fractional flow reserve measurements in patients with stable coronary artery disease: insights from combined stenosis and microvascular resistance assessment

Abstract: Identification of epicardial disease severity by FFR is partly obscured by the microvascular resistance, which illustrates the necessity of combined pressure and flow measurements in daily practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 30 publications
5
69
0
1
Order By: Relevance
“…The relationship between angiographic stenosis severity and functional significance assessed by FFR and the mismatch between these 2 measures have been extensively investigated to optimize percutaneous coronary intervention (PCI) 16, 24, 25, 26. Clinical factors, including age, sex, angiographical lesion‐related factors, and physiological factors, have been reported to contribute to visual‐functional mismatch and reverse mismatch 15, 16, 26, 27, 28. Our results were in line with these previous studies and further suggested the importance of microvascular function in both mismatch and reverse mismatch.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between angiographic stenosis severity and functional significance assessed by FFR and the mismatch between these 2 measures have been extensively investigated to optimize percutaneous coronary intervention (PCI) 16, 24, 25, 26. Clinical factors, including age, sex, angiographical lesion‐related factors, and physiological factors, have been reported to contribute to visual‐functional mismatch and reverse mismatch 15, 16, 26, 27, 28. Our results were in line with these previous studies and further suggested the importance of microvascular function in both mismatch and reverse mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that microvascular resistance independently and significantly influences visual‐functional mismatch and reverse mismatch in a large study population with intermediate epicardial coronary stenosis. Because FFR relies on a translesional hyperemic pressure gradient in a restricted model of coronary physiology, it is inevitably influenced by pharmacologically induced hyperemic coronary flow or by the individual's responsiveness to vasodilator drugs 15. The most important factor related to outcome in patients with coronary heart disease is the presence or absence of inducible myocardial ischemia and its extent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Identification of microvascular dysfunction, in addition to FFR, is essential to guide clinical management in a judicious manner. [25][26][27] Furthermore, impaired vasomotor function is a significant prognostic predictor, suggesting that myocardial perfusion is relevant despite the value of FFR. as the optimal cutoff value to detect hemodynamically significant CAD based on an FFR cutoff value of 0.80.…”
Section: Rfr Versus Ffrmentioning
confidence: 99%